Waterfowl at Cold Bay, Alaska, with notes on the display of the Black Scoter - McKinney, Frank (Wildfowl, 1959)
In 1958, it was my good fortune to spend April and May in the area of Cold Bay, near the tip of the Alaska Peninsula, studying waterfowl. For the waterfowl enthusiast, Alaska will always hold a special fascination. This is the home of the Emperor Goose (Anser canagicus), the Pacific Brant (Branta bernicla orientalis), the Spectacled Eider (Somateria fischeri) and Steller's Eider (S. stelleri)--birds which relatively few ornithologists have seen in the wild but which are familiar to many through the writings of Brandt (1943), Bailey (1948) and most recently Fisher and Peterson (1955). The main object of this expedition was to investigate the spring behaviour of Steller's Eider and of the Pacific Eider (Somateria mollissima v-nigra), and if possible to see something of King Eider and Spectacled Eider as well. I was particularly interested in the hostile and sexual behaviour which occurs before breeding and for this reason a centre for wintering birds was chosen in the belief that much of the pair-formation and related activities would occur before the birds moved to their breeding places. Cold Bay proved to be an ideal headquarters for these studies and during April I was able to watch large numbers of wintering Steller's on Izembek Bay; in May I camped in the middle of a large colony of Pacific Eiders at Nelson Lagoon when breeding was about to begin. My observations on these two species are being incorporated in a detailed analysis of Eider displays, not yet completed. Here I provide a record of the waterfowl species seen and report in detail on the displays of the Black Scoter (Melanitta nigra americana).